Tax Policy and Labor Market Performance - Lans Bovenberg (Center for Economic Studies and ifo Institute (CESifo), 2003)
In exploring the impact of tax policy on labor-market performance, the paper first investigates how tax reform impacts labor supply and equilibrium unemployment in representative agent models. The impact of tax policy on labor market performance depends importantly on various other labor-market institutions, such as minimum wage laws, wage bargaining, and unemployment benefits. In non-competitive labor markets, employment declines if a higher tax burden makes the outside option (i.e. unemployment) relatively more attractive. Marginal tax rates typically differ substantially across individuals. To explore the impact of specific tax policies, therefore, the paper relies on an applied general equilibrium model to investigate the consequences of tax reform with heterogeneous households. The model simulations reveal several trade-offs between various objectives, such as cutting unemployment, stimulating the participation of secondary workers into the labor force, raising the quality and quantity of labor supply, and establishing an equitable income distribution. The paper also analyses how efficiency considerations affect the optimal progressiveness of labor income taxes. Finally, the optimal progression of the labor income tax is investigated in the presence of search unemployment, heterogeneous households and distributional concerns.
Keywords: 330